High Levels of Cardiovascular Risk Factors among Pakistanis in Norway Compared to Pakistanis in Pakistan - Naeem Zahid; Haakon E. Meyer; Bernadette N. Kumar; Bjørgulf Claussen; Akhtar Hussain (Journal of Obesity)
Objectives. Previous studies have shown that the Norwegian-Pakistanis had considerably higher prevalence for diabetes and obesity compared to Norwegians. We studied the additional risk of obesity, dyslipidemia, and hypertension among Pakistanis in Norway compared to Pakistanis living in Pakistan. Method. 770 Norwegian-Pakistani adults (53.9% men and 46.1% women) born in Pakistan from two surveys conducted in Norway between 2000 and 2002 were compared with a sample of 1230 individuals (29.1% men and 70.9% women) that participated in a survey in Pakistan in 2006. Results. Both populations had similar height, but Norwegian-Pakistanis had considerably higher mean weight. Of the Norwegian-Pakistanis, 56% of the males and 40% of the females had a BMI above 25 kg/m2, as opposed to 30% and 56% in Pakistan, for males and females, respectively. Norwegian-Pakistanis had higher total cholesterol. Conclusion. Obesity and an unfavourable lipid profile were widely prevalent in both populations; the highest level was recorded amongst those living in Norway. The increased risk for obesity and dyslipidemia may be ascribed to change of lifestyle after migration.